2009
DOI: 10.3174/ajnr.a1643
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Perianeurysmal Edema Following Bare Platinum Embolization of a Small Unruptured Cerebral Aneurysm

Abstract: SUMMARY:There is considerable interest in the development of symptomatic inflammatory reactions following coil embolization of cerebral aneurysms. Patients have experienced a range of adverse events, usually after treatment of moderately large aneurysms with modified "bioactive" coils. More recently, it has been recognized that adverse inflammatory reactions can be associated with the use of "nonbioactive" coils, and we present a case of symptomatic perianeurysmal edema after treatment of a small unruptured an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…9,10 Our study showed that while perianeurysmal edema can occasionally occur following flow diversion, it is usually mild.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Our study showed that while perianeurysmal edema can occasionally occur following flow diversion, it is usually mild.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly inflammatory-mediated complications, such as edema visible under magnetic resonance imaging [3][4][5][6][7], aseptic meningitis [8][9][10], and communicating hydrocephalus [5,11,12], have been observed after embolization of unruptured aneurysms. While hydrocephalus after subarachnoid hemorrhage (SAH) is a common and well described, if not well understood, phenomenon [13]; the occurrence of hydrocephalus following treatment of unruptured aneurysms is unexpected.…”
Section: Introductionmentioning
confidence: 99%
“…These early-onset cases seemingly have no relationship to resolution; one case with PAVO onset at day 4 resolved at day 9,15 one case with PAVO onset day 1 remained present and stable at 12 months,4 and the remainder of these early onset cases resolved within 1–5 months. The majority of the remainder of the published cases have PAVO onset within 1–4 weeks12 or beyond 1 month4 7 8 16 and either resolve or near completely resolve by 5–12 months 7 8 12 16. Of eight cases not associated with aneurysm recanalisation, maximal PAVO was observed at a median of 6 months (range 1–6), and complete resolution was seen in four cases at 5, 6, 11 and 61 months, with a further one being partially resolved at 12 months and the remaining three remaining stable with follow-up of 6, 12 and 36 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…PAVO-related seizures were successfully treated with anticonvulsants alone,12 corticosteroids alone8 or as a combination 16…”
Section: Discussionmentioning
confidence: 99%